Conversor boost para mitigação de afundamentos de tensão em acionamentos de velocidade variável - Melo, Nelber Ximenes (2016)
This work investigates the effects of voltage sags on Adjustable Speed Drives – ASDs of AC machines, static converters of two stages (rectifier-inverter) widely used on speed and torque control. The goal is to analyse the behavior of the ASDs under symmetrical and asymmetrical voltage sags and the approaches to improve the ASD low voltage ride-through capability with emphasis to the boost converter technique. Computational simulations and experimental results of a boost converter designed to operate when the ASD is under voltage sags are presented. The tolerance curves of the ASD were obtained in laboratory for voltage sags types A, B and E and compared to the SEMI F47 0706 curve of the EPRI institute. The ASD was shown sensitive for voltage sags types A and E with immunity for remaining voltages up to 0.7pu on the DC link. Experimental tests were performed to evaluate the response of the boost converter operation when the ASD is under severe voltage sag conditions of types A and E. The set ASD-induction motor was modelled for the simulation tests and the model validation was performed by comparison with experimental results. The analysis of the ASD and the three-phase induction motor under voltage sags B, C, D, F e G were carried out by computational simulations. The voltage sag types A, E, F and G which can turn off the ASD were also analyzed by computational simulation with the boost converter connected to ASD DC bus. The curves of DC link voltage, the ASD output voltage, the boost input voltage and the input currents of the ASD, the boost converter and the source were plotted for evaluation of the ASD behavior with and without the boost converter. The simulation and experimental results have shown that the boost converter can mitigate voltage sags type A up to 0.5pu and all other types of voltage sags up to 0pu. The boost converter has proved a suitable solution to improve the ASD voltage sag ride through capability.